1994
DOI: 10.1097/00001888-199402000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Residency directorsʼ responses to the concept of a proposed electronic residency application service

Abstract: It is appropriate for the AAMC to take the lead in investigating the computerization of this important process. It is essential, however, to gather data from all three consumers of this potentially valuable service as an important step in the project's development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Since 1995, this activity has been facilitated by the Electronic Residency Application Service (ERAS) platform. 13 The second component in this sequence involves interviews of a select contingent of invited applicants by GME programs. 4 The third and final element of this progression involves the compilation of rank-ordered preference lists by both applicants and GME programs, the algorithmic reconciliation of which yields a “match.” Since 1952, the placement of U.S. medical students with allopathic residency programs has been ably carried out by the National Resident Matching Program (NRMP, the Match).…”
mentioning
confidence: 99%
“…Since 1995, this activity has been facilitated by the Electronic Residency Application Service (ERAS) platform. 13 The second component in this sequence involves interviews of a select contingent of invited applicants by GME programs. 4 The third and final element of this progression involves the compilation of rank-ordered preference lists by both applicants and GME programs, the algorithmic reconciliation of which yields a “match.” Since 1952, the placement of U.S. medical students with allopathic residency programs has been ably carried out by the National Resident Matching Program (NRMP, the Match).…”
mentioning
confidence: 99%
“…During the last several years, questions have been raised about the process and criteria that are used in the selection of applicants for orthopaedic residency programs, and it has been suggested that this process needs to be critically examined and revised [1][2][3][4][5] . In an effort to improve the resident-selection process, the factors involved in the recruitment of residents have been extensively studied for over thirty years 1,2,4,[5][6][7][8][9][10] .…”
mentioning
confidence: 99%
“…In an effort to improve the resident-selection process, the factors involved in the recruitment of residents have been extensively studied for over thirty years 1,2,4,[5][6][7][8][9][10] . Most practical information about resident-selection criteria that is accessible to program directors, applicants, and medical school advisors is acquired from surveys of residency program directors 5 .…”
mentioning
confidence: 99%
“…Further investigations under the auspices of the Association of American Medical Colleges 2,3 verified that the majority of residency program directors for both obstetrics-gynecology and family medicine supported the initiation and use of an online, computerized residency application process via a centralized Electronic Residency Application Service (ERAS). Graduating medical students applying for first-year residency positions in obstetrics-gynecology in 1995-1996 took part in a large-scale pilot test of ERAS in 150 participating programs.…”
Section: Introductionmentioning
confidence: 99%